Деформаційні процеси в музейництві: західноукраїнські області в 1939–1950-х рр. - Маньковська, Р.; Жиленкова, І. (Краєзнавство, 2018)
У статті досліджується широкий спектр ставлення комуністичного режиму до музеїв на
західноукраїнських землях, які, після входження їх до УРСР, опинилися в жорстких лещатах партійних органів та НКВС-МДБ. Висвітлюються наслідки ідеологічного тиску на діяльність музейних працівників, вилучення цілого пласта культурної національної спадщини через знищення унікальних пам'яток музейної скарбниці. The article presents different attitudes of the Communist regime to the museums of L’viv, Ternopil, Ivano-
Frankivsk, Rivne territories and Volyn, Bukovyna and Trans Carpathians which on their inclusion into the Ukrainian
Soviet Socialist Republic appeared within the hard grips of the Party bodies and under the sight of the NKVD. The
fatal consequences of ideological pressure on the activities of museum workers, the seizure of the whole stratum of
cultural national heritage through the destruction of unique monuments of the museum treasury are highlighted in
the article. The tragic events in the western regions, the consequences of which have long been concealed from society,
were manifested in the liquidation of private collections and the charitable support of museum institutions,
the nationalization or destruction of museum collections and their contents integrity, the «redevelopment» of museum
institutions or the elimination of many of them, the establishment of complete ideological control over museums. В статье исследуется отношение коммунистического режима к музеям на западноукраинских землях, которые, после вхождения их в УССР, находились в жестких тисках партийных органов и НКВД-МГБ. Освещаются последствия идеологического давления на деятельность музейных работников, извлечение пласта национального наследия через уничтожение уникальных музейных предметов.